The The Role of Traditional Food Menu in Improving NTT Cultural Tourism Promotion at Sylvia Kupang Hotel - Zakharia, Friend; Milyardo, Boiris; Flora, Veronika (International Journal of Applied and Advanced Multidisciplinary Research, 2024)
This research entitledthe role of traditional food menu’s as accultural promotion medium (case study on Hotels Sylvia kupang )based on the problem as we usually know in the sale of food products in the hotel industry,it canot be separated from the sales of cultured menu’s such as chinese food,european food, Japanese food,and various other types of menu’s regardless of the potential pecualiarites of regional food.this study aims to determine the role of tradisional food menu’s as a medium for cultural promotion. Data collection was carried out by documentation,direct observation and olso interviews with several   informant, namely departie chef and manager of food and beverage related to traditional food menu’s sold in Sylvia Kupang Hotel then processed the data correctly according to the data obtained from the Hotel Sylvia Kupang.The conclusion from the results of the data concludedthat the role of traditional food menu’sas a media for cultural promotion in Slyvia Hotel has its own charm for local guests,outside the region or abroad. Because of its uniquenessand distinctive characteristics that distinguish it from other food menu’s that are always sought after by guests who come to stay at Sylvia Hotel. And also promoting traditional food that is characterized by regional specialties throughelectronic media namelywhatsapp,instagram,and facebookto the general public. So the traditional food is growing and its existence is preserve.